Genome wide profiling of miRNAs relevant to the DNA damage response induced by hexavalent chromium exposure (DDR-related miRNAs in response to Cr (VI) exposure). (December 2021) - Shi, Li; Feng, Lingfang; Tong, Yan; Jia, Junlin; Li, Tao; Wang, Jing; Jiang, Zhaoqiang; Yu, Min; Xia, Hailing; Jin, Qi; Jiang, Xiyi; Cheng, Yongran; et al.
Graphical abstract: Highlights: Cr (VI) exposure caused miRNAs dysregulation in vitro and in electroplating workers. DNA damage response was associated with one or more miRNAs expression. Functional study revealed differentially expressed miRNAs might play roles in DDR. Abstract: Aim: We aimed to explore the expression of miRNAs and their potential roles in the DNA damage response (DDR) induced by Cr (VI) exposure in human B lymphoblast cells (HMy2.CIR cells) and in a population of Cr (VI)-exposed humans. Methods: Differentially expressed miRNAs were found by a combination of miRNA sequencing and RT-qPCR validation in HMy2.CIR cells treated with K2 Cr2 O7 . Differentially expressed miRNAs related to DDR were selected for functional study. The expression levels of differential miRNAs were also investigated in chromate workers. Results: A total of 214 differentially expressed miRNAs were identified by sequencing, and the expression of 5 miRNAs among 25 associated with DDR was found to be consistent between sequencing and validation studies. Functional studies showed that miR-148a-3p, miR-21-5p, and miR-424-3p might be related to Cr (VI)-induced cell apoptosis, and miR-221-3p might participate in Cr (VI)-induced DDR. We also found that the expression of miR-21-5p and miR-424-3p was upregulated in chromate workers. Conclusions: Cr (VI) exposure could significantly impact miRNAs expression in vitro and in chromate workers. Functional studies showed that miR-148a-3p, miR-21-5p and miR-221-3p might take a crucial role in the cellular DDR induced by Cr (VI) exposure.